International Conference on the Epidemiology and Control of Biological, Chemical and Physical Hazards in Pigs and Pork 2015
DOI: 10.31274/safepork-180809-330
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of antibiotic use after implementation of Ingelvac® PRRS MLV piglet vaccination in a Belgian wean to finish farm

Abstract: Porcine Reproductive and Respiratory Syndrome (PRRS) infections play an important role in Porcine Respiratory Disease Complex (PRDC). The aim of this study was to evaluate the effect of implementing a PRRS MLV vaccine, as an aid to control PRDC, on the antibiotic use in piglets and fatteners. The study was performed in a wean-to-finish farm. Piglets were vaccinated upon arrival. In 2012, piglets were only vaccinated against Mycoplasma hyopneumoniae (M. hyo) with Ingelvac MycoFLEX®. As from 2013, Ingelvac® PRRS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…For example, vaccination against Porcine Circovirus Type 2 (PCV-2), which is an immune-suppressive viral infection leading to secondary bacterial infections, resulted in a significant diminution of antibiotic use in swine farms (Raith et al, 2016). Similarly, vaccination against Porcine Reproductive and Respiratory Syndrome (PRRS) virus on pig farms reduced antibiotic consumption (Van Looveren et al, 2015). Amongst important bacterial pathogens of swine, vaccination against Lawsonia intracellularis, which causes severe ileitis, has been reported to reduce oxytetracycline medication in pigs (Bak and Rathkjen, 2009), whilst immunization against the respiratory pathogen Actinobacillus pleuropneumoniae also reduced administration of antibiotics (Kruse et al, 2015).…”
Section: Alternatives To Antibioticsmentioning
confidence: 99%
“…For example, vaccination against Porcine Circovirus Type 2 (PCV-2), which is an immune-suppressive viral infection leading to secondary bacterial infections, resulted in a significant diminution of antibiotic use in swine farms (Raith et al, 2016). Similarly, vaccination against Porcine Reproductive and Respiratory Syndrome (PRRS) virus on pig farms reduced antibiotic consumption (Van Looveren et al, 2015). Amongst important bacterial pathogens of swine, vaccination against Lawsonia intracellularis, which causes severe ileitis, has been reported to reduce oxytetracycline medication in pigs (Bak and Rathkjen, 2009), whilst immunization against the respiratory pathogen Actinobacillus pleuropneumoniae also reduced administration of antibiotics (Kruse et al, 2015).…”
Section: Alternatives To Antibioticsmentioning
confidence: 99%
“…Several studies have demonstrated the potential of vaccines to achieve a significant reduction of antimicrobial consumption in swine herds [ 26 , 27 ]. Vaccination of pigs against different pathogens as Actinobacillus pleuropneumonia [ 28 ], Lawsonia intracellularis [ 29 ], porcine circovirus type 2 [ 30 , 31 ], porcine reproductive and respiratory syndrome virus [ 32 ] can lead to the remarkable decrease of AMU. The effect of vaccination in swine herds on the use of polymyxins has been studied in combination with other alternatives [ 33 ].…”
Section: Introductionmentioning
confidence: 99%